Analysis of Strategies to Overcome the Negative Stigma of Recycled MSME Products: A Case Study of Used Tire Waste Processing in Sidenreng Rappang Regency - Suriadi, Suriadi; Salam, Mifta Farid; Salida, Amrizal; Heady S, Muhammad G.Try; Sampara, Nirwana (Amkop Management Accounting Review (AMAR), 2025)
The implementation of a circular economy holds significant potential to support environmental sustainability and economic growth. However, it still faces key challenges, particularly the negative public stigma toward recycled products and a sense of social prestige that discourages people from using them. Therefore, this study aims to conduct an in-depth analysis and identify solutions to address these issues. This research employs an exploratory qualitative method with a case study approach, focusing specifically on micro, small, and medium enterprises (MSMEs) that process tires in Sidenreng Rappang Regency. Data were collected through observation, semi-structured interviews, and documentation. Informants were selected using purposive sampling, snowball sampling, and convenience sampling. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing and verification. To ensure data validity, triangulation was carried out by comparing information. The findings reveal that the implementation of a circular economy through used tire recycling businesses in Sidenreng Rappang still faces several obstacles, particularly in production due to limited raw materials; in marketing, which remains suboptimal and highly dependent on intermediaries; and in financing, as business capital is constrained by the lack of accessible funding support. On the other hand, public stigma toward recycled products is driven more by psychological and cultural factors—especially feelings of social prestige—rather than by product quality, which is actually quite good and durable. According to, MSMEs require tangible support in the form of easier access to capital, broader promotional efforts, and affirmative policies from local governments. Meanwhile, strategies to reduce stigma can be implemented through improving product quality and providing warranties, public education, stronger branding, the use of digital marketing, and active government involvement in promotion and supportive regulations.